Interaksi Sosial Siswa di SLB YKB Talawi - Indra Yeni; Muhammad Bayu Septian; Zikra Yafi Nurullah; Prasetya Aldi Rivalni; Aulia Rahmi5 (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This research is an observational study conducted by students of the Community Service Program (KKN) from Universitas Negeri Padang in Desa Salak, Talawi Subdistrict, Sawahlunto City. It aims to describe the forms of social interaction among students at Sekolah Luar Biasa (SLB) YKB Talawi. Social interaction is a crucial aspect of the socio-emotional development of children with special needs, particularly in shaping their independence and social skills. The observation was carried out during several school activities, including the introductory session between KKN students and SLB students, an explanation by the teacher regarding the school, the Dhuha prayer activity, recess time, and when students ate their packed meals. The findings show that students engaged in various forms of social interaction, including simple verbal and nonverbal communication, responses to teacher instructions, and peer interactions in an atmosphere of tolerance and emotional support. The interaction patterns were influenced by the type of special needs, the nature of the activities, and the communication approaches used by teachers and KKN students. These findings are expected to serve as an initial reference for understanding social dynamics in special education settings and highlight the importance of adaptive approaches in fostering the social development of children with special needs.